Preterm prelabor rupture of membranes after fetoscopic laser surgery for twin–twin transfusion syndrome. (May 2017) - Snowise, S.; Mann, L. K.; Moise, K. J.; Johnson, A.; Bebbington, M. W.; Papanna, R.
ABSTRACT: Objective: To assess the incidence, clinical course, risk factors and outcomes of preterm prelabor rupture of membranes (PPROM) after fetoscopic laser surgery (FLS) for twin–twin transfusion syndrome (TTTS). Methods: This was a prospective observational cohort study of 154 consecutive cases of TTTS. PPROM was defined as rupture of membranes before 34 weeks' gestation. Procedure‐to‐PPROM and PPROM‐to‐delivery intervals were determined. Relevant preoperative and intraoperative variables were analyzed by univariate and multivariate logistic regression to determine their impact on PPROM after FLS. Results: The incidence of PPROM was 39% ( n  = 60), occurring at a mean gestational age of 27.2 ± 4.6 weeks. Median procedure‐to‐PPROM interval was 46 (range, 1–105; interquartile range (IQR), 13–66) days and median PPROM‐to‐delivery interval was 1 (range, 0–93; IQR, 0–13) day. Mean gestational age at delivery in cases with PPROM was 29.0 ± 4.5 weeks compared with 32.6 ± 3.9 weeks in cases without PPROM ( P  < 0.0001). Insertion of a collagen plug was the only significant factor found on both univariate and multivariate analysis to be associated with an increased rate of PPROM (odds ratio, 3.1 (95% CI, 1.2–8.0); P  = 0.006). There was no statistically significant difference in fetal ( P  = 0.07) or neonatal ( P  = 0.08) survival between those with and those without PPROM. Conclusions: PPROM after FLS increases prematurity by 3.6 weeks. The latency period after PPROM was 2 weeks; 50% of patients delivered within 24 h. No variable thought to be associated with PPROM after FLS was found to be significantly associated with this complication. Other etiologies and mechanisms for PPROM after FLS should be explored. Copyright © 2016 ISUOG. Published by John Wiley & Sons Ltd.